(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Oesophagogastrostomy is a very crucial surgical management. Objective:The purpose of the present study was to observe the immediate post-operative outcomes of stapled and hand sewn techniques during oesophagogastrostomy. Methodology: This single centre, parallel randomized clinical trial was conducted in the Department of Thoracic Surgery at National institute of Diseases of the Chest and Hospital, Dhaka, Bangladesh from January 2011 to December 2011 for a period of one year. Prior to commencement of this study the study protocol was approved by the thesis committee of NIDCH. Patients were purposefully selected from different surgery ward of NIDCH irrespective of age and sex of patients for the study.Patients were divided into two groups designated as group A and B.Stapled oesophagogastric anastomosis was performed in group A and hand sewn anastomosis was done in group B.Immediate post-operative complication were recorded. Result: A total of 60 patients of oesophageal or gastric cardia carcinoma were recruited for this study. Of them 32 cases were assigned to Stapler method and 28 cases to Hand-sewn method of oesophagogastrostomy. The mean age of the patients of group A and group B were 56.1±12.7 years and 55.3±8.3 years respectively. Regarding blood loss during operation, the table shows that in group A mean + SD were 430.4±63.2 ml and in group B mean + SD were 529.6 +86.9 ml. In one stage operation in group A it was mean + SD i.e. 362.2±38.3 ml and in group B it was mean + SD 529.6±86.9 ml. In two stage operation in group A it was mean 466.2±39.7 ml and in group B it was mean±SD 585.6±62.2 ml. Respiratory complication developed in 9.4% of the patients in group A and 17.9% patients in group B. Cardiac complication developed in 3.1 % of the patients in group A and 7.1 % of patients in group B. Wound infection developed in 12.5% of the patients in group A and 10.7% of the patients in group B. Conclusion: In conclusion most of the immediate anastomotic complications are less in stapled anastomotic technique than hand sewn technique Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 43-47